2020
DOI: 10.1038/s41587-020-0600-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of AsCas12a for combinatorial genetic screens in human cells

Abstract: Cas12a RNA-guided endonucleases are promising tools for multiplexed genetic perturbations because they can process multiple guide RNAs expressed as a single transcript and subsequently cleave target DNA. However, their widespread adoption has lagged behind Cas9-based strategies due to low activity and the lack of a well-validated pooled screening toolkit. Here we describe the optimization of enhanced AsCas12a (enAsCas12a) for pooled, combinatorial genetic screens in human cells. By assaying the activity of tho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
183
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(211 citation statements)
references
References 49 publications
7
183
0
Order By: Relevance
“…Importantly, by comparing the mean log fold change of query gene knockouts in the “A” position vs . the same genes in the “B” position of the dual knockout vector, we find no positional bias in the multiplex knockout constructs ( Figure 4d ), consistent with our previous findings 23,34 . Single knockout fitness measurements effectively segregated known essential genes from nonessentials, confirming the efficacy of the primary screens ( Supplementary Figure 6 ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Importantly, by comparing the mean log fold change of query gene knockouts in the “A” position vs . the same genes in the “B” position of the dual knockout vector, we find no positional bias in the multiplex knockout constructs ( Figure 4d ), consistent with our previous findings 23,34 . Single knockout fitness measurements effectively segregated known essential genes from nonessentials, confirming the efficacy of the primary screens ( Supplementary Figure 6 ).…”
Section: Resultssupporting
confidence: 92%
“…Digenic perturbations in human cells, a more faithful replication of the yeast approach, are possible with Cas9 and its variants, but library construction, sequencing, and positional biases can be problematic 16,28–34 . Recently, we showed that an engineered variant of the Cas12a endonuclease, enCas12a 35 , could efficiently perform multiplex gene knockouts 34 , and we demonstrated its effectiveness in assaying synthetic lethality between targeted paralogs 23 . These developments in principle enable researchers to measure how biological networks vary across backgrounds, a powerful approach for deciphering complex biology 24,36,37 .…”
Section: Introductionmentioning
confidence: 99%
“…We manually added five additional candidate gene pairs from the literature: SMARCA2-SMARCA4, CDH1-CDH3, ME2-ME3, BCL2L1-MCL1, and BRCA1-PARP1, for a total of 405 targeted gene pairs. For each gene, up to three CRISPR RNA (crRNA) were selected using a library designed by DeWeirdt et al [28]. Each gene pair was targeted with all 9 combinations of guides, in both A-B and B-A orientations, for a total of 18 clones targeting each pair.…”
Section: Resultsmentioning
confidence: 99%
“…This makes multiplexing much easier compared to inefficient Cas9 based multiplex systems which requires each guide RNA to be expressed by its own promoter. The improved version of this enzyme, enCas12a [22], coupled with an effective guide design algorithm [28] presents a powerful platform for multiplex genetic perturbation. Multiplex guide libraries can be synthesized directly, without requiring additional targeted or random mixing cloning steps, allowing direct assay of specific gene pairs as described here with roughly the same level of effort as a now-standard Cas9 monogenic screen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation